Balancing Cholesterol Synthesis and Absorption in the Gastrointestinal Tract - Cohen, David E. (2008)
Cholesterol balance is achieved both by synthesis in the body and by absorption in the gastrointestinal tract. Cholesterol synthesis and absorption are also critical determinants of plasma LDL cholesterol concentrations. In clinical practice, inhibitors of synthesis and inhibitors of absorption are both effective methods of lowering LDL cholesterol concentrations and may be utilized in combination. This review rationalizes these mechanisms of LDL reductions by placing them in the context of cholesterol balance as it is determined by digestive lipid metabolism.